2020
DOI: 10.1155/2020/8816598
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Surgical Treatment of Thoracic Dorsal Arachnoid Web: A Report of Two Cases

Abstract: Introduction. An arachnoid web (AW) is a relatively rare disease and shows clinical symptoms and radiological findings similar to those of an arachnoid cyst (AC) or spinal cord herniation (SCH). Since the operative procedures for an AW are generally different from those intrathecal disorders, correct preoperative differential diagnosis is important. The purposes of this study were to report the usefulness of magnetic resonance imaging (MRI) and computed tomography (CT) myelography for diagnosing AW and to show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…While there is no pathological definition of the arachnoid web, the arachnoid membrane-like epithelial tissue observed in our specimen was consistent with that previously described. 11) In the arachnoid web diagnosis, the important finding of "scalpel sign" was found on the MR images, which indicated the dorsal indentation of the spinal cord. Thus, our case corresponded to the entity of the arachnoid web.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is no pathological definition of the arachnoid web, the arachnoid membrane-like epithelial tissue observed in our specimen was consistent with that previously described. 11) In the arachnoid web diagnosis, the important finding of "scalpel sign" was found on the MR images, which indicated the dorsal indentation of the spinal cord. Thus, our case corresponded to the entity of the arachnoid web.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no pathological definition of the arachnoid web, the arachnoid membrane-like epithelial tissue observed in our specimen was consistent with that previously described. 11 )…”
Section: Discussionmentioning
confidence: 99%
“…Arachnoid web should be differentiated from ventral cord herniation and arachnoid cyst [5] and can be diagnosed radiologically by the characteristic feature scalpel sign [6]. It usually manifests as symptoms of progressive myelopathy and can be treated successfully with surgical removal [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this intermedullary CSF pressure gradient can result in syringomyelia. The typical location of syringomyelia is either rostral or caudal to the arachnid web because the specific structure of arachnoid web can promote one-way flow of CSF and unidirectional syringomyelia [7].…”
Section: B Amentioning
confidence: 99%
“…Innou et al 14 and Ben Ali et al 3 concluded that a change of arachnoid after infection or trauma might lead to SAW. In a histopathological analysis of SAW connective tissue, Chang et al 6 found small numbers of CD3 + T cells.…”
Section: Pathophysiologymentioning
confidence: 99%